Interferonβ-1b Induces the Expression of RGS1 a Negative Regulator of G-Protein Signaling. (26th October 2010) - Tran, Tiffany; Paz, Pedro; Velichko, Sharlene; Cifrese, Jill; Belur, Praveen; Yamaguchi, Ken D.; Ku, Karin; Mirshahpanah, Parham; Reder, Anthony T.; Croze, Ed
Abstract : We present evidence of a link between interferon β -1b (IFN- β ) and G-protein signaling by demonstrating that IFN- β can induce the expression of the negative regulator of G-protein signaling 1 (RGS1). RGS1 reduces G-protein activation and immune cell migration by interacting with heterotrimeric G-proteins and enhancing their intrinsic GTPase activity. In this study, IFN- β treatment resulted in the induction of RGS1 in peripheral blood mononuclear cells (PBMCs), monocytes, T cells, and B cells. Induction of RGS1 by IFN- β was concentration dependent and observed at both the RNA and protein level. Other members of the RGS family were not induced by IFN- β, and induction of RGS1 required the activation of the IFN receptor. In addition, RGS1 induction was observed in PBMCs obtained from IFN- β -treated multiple sclerosis patients suggesting a possible, as yet unexplored, involvement of G-protein regulation in disease treatment. The upregulation of RGS1 by IFN- β has not been previously reported.